Association between periodontal diseases and cardiovascular diseases in Cameroon - Lawrence Essama Eno Belinga; Williams Bell Ngan; Daniel Lemougoum; Alain Serges Patrick Essam Nlo'o; Bienvenu Bongue; Annie Ngono; Samuel Honoré Mandengue; Malick Sembene (AOSIS, 2018)
To assess the association between periodontal diseases and cardiovascular diseases in dental patients in Cameroon, a prospective observational study was carried out in 3 hospitals in Cameroon from January 2013 to December 2015. Data on general condition, age, gender and lifestyle were collected during medical history taking. The Dutch Periodontal Screening Index assessed periodontal health during oral examination. The Wilcoxon test, the Fisher test and logistic regression analysis were performed. 558 patients (53.9% women) were included in the study. The mean age was 44±13 years (30 to 85). In terms of overall health, 161 (28.9%) had cardiovascular diseases (CVD) and 73 (13.1%) had diabetes. Hypertension accounted for 87.6% of CVD. In terms of periodontal diseases (PD), 431 (77.2%) patients had PD, the break-down by PD was 347 (62.2%) gingivitis and 84 (15%) periodontitis. Statistical associations were found between CVD and gingivitis [OR=4.30 (1.85-10.00), P=0.001], and CVD and periodontitis [OR=2.87 (1.04-7.93); P=0.04].